Detailed experimental validation and benchmarking of six models for longitudinal tensile failure of unidirectional composites. (1st January 2022) - Breite, C.; Melnikov, A.; Turon, A.; de Morais, A.B.; Le Bourlot, C.; Maire, E.; Schöberl, E.; Otero, F.; Mesquita, F.; Sinclair, I.; Costa, J.; Mayugo, J.A.; et al.
Abstract: Longitudinal tensile failure of unidirectional fibre-reinforced composites remains difficult to predict accurately. The key underlying mechanism is the tensile failure of individual fibres. This paper objectively measured the relevant input data and performed a detailed experimental validation of blind predictions of six state-of-the-art models using high-resolution in-situ synchrotron radiation computed tomography (SRCT) measurements on two carbon fibre/epoxy composites. Models without major conservative assumptions regarding stress redistributions around fibre breaks significantly overpredicted failure strains and strengths, but predictions of models with at least one such assumption were in better agreement for those properties. Moreover, all models failed to predict fibre break (and cluster) development accurately, suggesting that it is vital to improve experimental methods to characterise accurately the in-situ strength distribution of fibres within the composites. As a result of detailed measurements of all required input parameters and advanced SRCT experiments, this paper establishes a benchmark for future research on longitudinal tensile failure.